Introducing health technology assessment in Tanzania. (12th April 2020) - Surgey, Gavin; Chalkidou, Kalipso; Reuben, William; Suleman, Fatima; Miot, Jacqui; Hofman, Karen
Abstract: Objectives: Health technology assessment (HTA) is a cost-effective resource allocation tool in healthcare decision-making processes; however, its use is limited in low-income settings where countries fall short on both absorptive and technical capacity. This paper describes the journey of the introduction of HTA into decision-making processes through a case study revising the National Essential Medicines List (NEMLIT) in Tanzania. It draws lessons on establishing and strengthening transparent priority-setting processes, particularly in sub-Saharan Africa. Methods: The concept of HTA was introduced in Tanzania through revision of the NEMLIT by identifying a process for using HTA criteria and evidence-informed decision making. Training was given on using economic evidence for decision making, which was then put into practice for medicine selection for the NEMLIT. During the revision process, capacity-building workshops were held with reinforcing messages on HTA. Results: Between the period 2014 and 2018, HTA was introduced in Tanzania with a formal HTA committee being established and inaugurated followed by the successful completion and adoption of HTA into the NEMLIT revision process by the end of 2017. Consequently, the country is in the process of institutionalizing HTA for decision making and priority setting. Conclusion: While the introduction of HTA process is country-specific, key lessons emerge that can provide an example to stakeholders in other low- and middle-income countries (LMICs) wishing to introduce priority-setting processes into health decision making.